Evaluation of the Leishmanicidal potential of ethanolic extracts derived from Cymbopogon citratus leaves and Ganoderma lucidum fruiting bodies on Leishmania martiniquensis promastigotes - W, Chimyaem; V, Kluabwang; V, Santiwong; N, Intakhan; C, Mano; A, Junkum; N, Jariyapan (Biomedical Sciences and Clinical Medicine, 2019)
Objective To evaluate the leishmanicidal potential of ethanolic extracts derived from Cymbopogon citratus leaves and Ganoderma lucidum fruiting bodies on Leishmania martiniquensis promastigotes. Methods The chemical composition of ethanolic extracts from C. citratus leaves and G. lucidum fruiting bodies were analyzed using gas chromatography-mass spectrometry (GC-MS) and their leishmanicidal potential was evaluated in vitro with L. martiniquensis promastigotes. The half maximal inhibitory concentrations (IC50) of the extracts was determined using alamarBlue Cell Viability Reagent. Cytotoxicity was tested on the human monocytic THP-1 cell line (THP-1 cells) and the selectivity indices (SI) of both extracts were calculated. Results GC-MS analysis identified 17 compounds in the ethanolic extracts of C. citratus and 25 in the extracts of G. lucidum representing 76.87 and 95.45%, respectively, of all the components in each of those extracts. D:A-friedoursan-3-one (17.49%) and ergosterin (36.90%) were the main constituents of the C. citratus and the G. lucidum extracts, respectively. The C. citratus extract demonstrated moderate leishmanicidal activity with an IC value of 20.26±2.8 μg/mL whereas the G. lucidum extract showed weak leishmanicidal activity (54.69±13.67 μg/mL). SI values of the extracts of C. citratus and G. lucidum were 5.38 and 3.54 μg/mL, respectively, showing that they were less toxic to THP-1 cells than to Leishmania parasites. Conclusion The ethanolic extract of C. citratus with an SI value<10 has greater leishmanicidal activity than G. lucidum. Further investigations are needed to separate, purify, and identify the active compo- nents of these two plant sources as the extracts are complex mixtures of substances and pertinent active compounds may be present in low concentrations.